2019
DOI: 10.1038/s41467-019-10932-4
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-binding to the cytoplasmic PAS domain regulates the essential WalK histidine kinase of Staphylococcus aureus

Abstract: WalKR (YycFG) is the only essential two-component regulator in the human pathogen Staphylococcus aureus . WalKR regulates peptidoglycan synthesis, but this function alone does not explain its essentiality. Here, to further understand WalKR function, we investigate a suppressor mutant that arose when WalKR activity was impaired; a histidine to tyrosine substitution (H271Y) in the cytoplasmic Per-Arnt-Sim (PAS CYT ) domain of the histidine kinase WalK. Introducing th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 68 publications
(87 reference statements)
2
48
0
Order By: Relevance
“…WalK has an extracytoplasmic and a cytoplasmic PAS domain, both being potential candidates for sensing ligands that control the phosphorylation activity. Crystallization of the cytoplasmic PAS domain revealed a Zinc atom binding site, which upon zinc-binding leads to a conformational change of WalK that inhibits WalRK phosphorylation [9]. Very recently it was shown that so far unidentified peptidoglycan degradation products modify the activity of B. subtilis WalK and might interact with the extracellular PAS domain [20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…WalK has an extracytoplasmic and a cytoplasmic PAS domain, both being potential candidates for sensing ligands that control the phosphorylation activity. Crystallization of the cytoplasmic PAS domain revealed a Zinc atom binding site, which upon zinc-binding leads to a conformational change of WalK that inhibits WalRK phosphorylation [9]. Very recently it was shown that so far unidentified peptidoglycan degradation products modify the activity of B. subtilis WalK and might interact with the extracellular PAS domain [20].…”
Section: Discussionmentioning
confidence: 99%
“…Work in B. subtilis indicates that the extracellular PAS domain might provide feedback information about the activity of the autolysins [20]. Zinc binding to the intracellular PAS domain is special for staphylococci and enterococci and inhibition by zinc was mainly observed at the entry into stationary phase [9], indicating that zinc might act to decrease activity of WalK at this time point. The role of the zinc signaling for S. aureus is unclear, but zinc is essential for S. aureus, a co-factor of some autolytic amidases [52] and plays a role in bacterial infection and innate immunity [53].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations